Framework for multi-fidelity simulations of flow interaction and noise of an open rotor - Huang, Guangyuan; Sharma, Ankit; Chen, Xin; Jimeno Altelarrea, Sergio; Riaz, Atif (American Institute of Aeronautics and Astronautics (AIAA), 2025)
Flow-induced noise from open rotor aircraft has received immense research interests as the flow interactions of the components of open rotors lead to significant non-linear features and the flow-induced noise is complicated. Numerical approaches for predicting open rotor flow interactions and the induced noise are in demand without compromising computational accuracy and reducing cost. In this paper, an existing multi-fidelity framework for propeller noise modelling is extended to open rotor configuration. A generic contra-rotating open rotor (CROR) configuration is developed to assess the capability of this multi-fidelity framework. The flow and noise of this configuration are modelled separately in hybrid manner. The flow solution is computed using two methods, which employ unsteady Reynolds average Navier-Stokes (URANS) equations and lattice-vortex method (VLM) at respectively higher- and lower-fidelity levels. Then, the acoustic solution is computed based on the flow solution using Gutin’s method. Results show that transonic features over the rotor blades and significant tip vortices in the wake characterise the CROR flow. Multi-rotor interactions are observed. The aerodynamic loadings are investigated in terms of their mean and fluctuating components. In addition, the far-field noise from the two rotors are compared. The present multi-fidelity framework will be used in future aircraft design which involves open rotor engines. This work is being administered as part of the Innovate UK, Aerospace Technology Institute (ATI) funded research project - ONEheart (Out of Cycle NExt generation highly efficient air transport).